NEED ANALYSIS OF INSTRUCTIONAL MEDIA FOR DEAD AND MENTALLY RETARDED AT SLBN LENGAYANG - Rasmita Rasmita; Dinda Djesmedi; Fitri Firdalius (Jurnal Ipteks Terapan (Research Of Applied Science And Education ), 2021)
This study aims to analyze students need in the first class at SLBN students in development of learning media on the material for the theme of myself with sub-theme of part of body. This research is descriptive qualitative. Needs analysis is done based on the results of interviews, questionnaire and direct observation. The purpose of this study is to analyze the need for multimedia-based learning media software in the form of applications on android. The application is used to assist teachers in delivering learning materials for the introduction of part of body in the first class at SLBN Lengayang consisting of deaf and mentally retarded students. To collect the data, the researchers used questionnaires, interviews and observations. The results of the needs analysis obtained are: 1) The learning media used is still a presentation media 2) There is still a lack of attractiveness and student activity in teaching and learning activities.